Religious Education Development At Private Tsanawiyah Madrasah Tunas Harapan Tembilahan Islamic Boarding School - Ruhiat, Ruhiat; Nur Laily, Elly; Junaidi, Junaidi; Wakhidati Purwaningsih, Tatik; Khalifah , Siti; Shaleha , Siti (Jurnal Masyarakat Mengabdi, 2024)
Students' lack of ability to read the Koran and practice prayer is one of the factors inhibiting student achievement in learning. Religious education development aims to improve students' ability to read the Quran and practice prayer. This method is implemented by holding evenings for building knowledge and piety in which there are several activities including, teaching the science of recitation, teaching the recitation of the Koran, teaching ablution, teaching prayer, and teaching wirid. Through evening activities for building faith and piety, teachers can have more freedom in developing students so that learning achievement can be achieved and can be measured according to predetermined standards. Through the guidance of evening activities for building faith and piety, students experience development and improvement in terms of tajwid knowledge, reading the Al-Qur'an, worship, and wirid.